Reforming Indonesia’s Correctional System: The Role of Maqāṣid Al-Syarīʿah in Ensuring Justice and Rehabilitation - Bunyamin, Bunyamin; Arifin, Firdaus; Maarif, Ihsanul; Bahri, Robi Assadul; Abdullah, Mohd Kamarulnizam (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2025)
The correctional system in Indonesia faces significant challenges, including overcapacity, low effectiveness of rehabilitation, and a lack of integration of spiritual values. This research aims to explore the application of maqāṣid al-syarīʿah as a value foundation in the reform of the correctional system to enhance the effectiveness of rehabilitation and reintegration of inmates. This research employs a qualitative method with a normative-empirical approach, encompassing an analysis of regulatory frameworks, particularly Law Number 22 of 2022 concerning Corrections and observational techniques. The research results show that maqāṣid al-syarīʿah, with principles such as the protection of life (hifz an-nafs), intellect (hifz al-aql), spirituality (hifz ad-din), lineage (hifz an-nasl), and property (hifz al-māl) provide a holistic framework to support the rehabilitation of prisoners. Programs based on religious values and practical skills have proven capable of supporting individual moral and economic changes, while community involvement through community mentors strengthens social reintegration. However, challenges such as limited resources, cultural resistance to religious-based approaches, and the lack of oversight based on maqāṣid al-syarīʿah indicators hinder optimal implementation. Therefore, this research recommends a revision of more specific regulations, including the provision of religious-based facilities, officer training, and the strengthening of technology-based evaluations. This research includes formulating more humane and inclusive correctional policies in line with Islamic values and universal human rights. By integrating maqāṣid al-syarīʿah, the correctional system in Indonesia can transform into an instrument that is punitive and rehabilitative, creating sustainable social harmony.